The perception of the teacher trainees on the implementation of e-assessment in the selected Teacher Training Colleges in Kenya - Kubai, Edwin (African Journal of Science, Technology and Social Sciences, 2024)
The Kenya National Examinations Council (KNEC) is currently implementing the integration of technology in conducting assessments to replace the traditional mode of paper and pen. The purpose of this study is to examine the perception of the teacher trainees towards the implementation of e-assessment in the upgrade course of the Diploma in Primary Teacher Education (UDPTE). The study adopted a descriptive research design and was carried out in two (2) public teacher training colleges with a target population of two hundred and forty (240) teacher trainees for the UDPTE programme. All the trainees in the sampled colleges were purposively selected to participate in the study since all of them had participated in the formative e-assessment. An online Teacher Trainees Questionnaire (TTQ) was used to collect information relating to trainees' perception of e-assessment. The reliability coefficient alpha (α) of TTQ was found to be 0.78 from the pilot study making the instrument valid for data collection. The data collected was analyzed using both descriptive and inferential statistics by the use of SPSS software version 26.0. The study findings established that a significant number of teacher trainees were upgrading in Option B as compared to Option A learning areas. The teacher trainees believed that the best way to finance the Upgrade of Diploma in Primary Teacher Education program (UDPTE) in Kenya was by using bursaries or scholarships and not loans. A significant number of teacher trainees support the adoption of e-assessment but they are of the view that the colleges were not yet prepared due to lack of necessary technological infrastructure. It was further noted that the teacher trainees need more training on basic computer skills in order to improve their typing skills for responses to enhance the complete submission of assessments on the portal in their respective learning areas. The Ministry of Education needs to equip the teacher training colleges with the necessary technological infrastructure and continuously retool tutors on how to integrate technology tools in the assessment procedures.